Dźwięki reaktywne, dźwięki antycypujące. Z zagadnień funkcjonowania ścieżki dźwiękowej w grach wideo - Pigulak, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The paper aims to outline features of video games’ sounds. In order to do that, the author presents the main thesis of ludomusicology and a theory of film music. The first part of the paper deals with a brief introduction concerning the characteristic of two important aspects of video games’ sounds: reactive and anticipating sounds. In the second part of the paper, the author explores the issue of facultative dialogues and adaptive sounds, as well as diegetic and non-diegetic sources of sound. The author examines the hypothesis that using sounds in video games determines gameplay and impacts players immersion.